A modified frozen elephant trunk hybrid device to facilitate supra‐aortic trunk anastomosis. Issue 1 (22nd November 2020) - Masiello, Paolo; Mastrogiovanni, Generoso; Chivasso, Pierpaolo; Triggiani, Donato; Cafarelli, Francesco; Iesu, Severino
Abstract: Reimplantation of the supra‐aortic vessels can be challenging with Thoraflex Hybrid. A device modification made the vessel lengths more appropriate and the position of the neo‐vessels in the chest avoided malpositioning and kinking and facilitated sternum closure; this may improve operating times as well as allowing complete and continuous cerebral trivascular perfusion and corrects positioning of the intrathoracic vessels.